A Filosofia Pragmatista na Educação Popular - Magalhães, Daniel Alves (2008)
The subject of this research is the Pragmatist Philosophy and its area of action is the Popular Education. Our aim is investigating the possibility of applying Pragmatist Philosophy in educational activities through the Popular Education. For doing so, we developed a study concerning the Pragmatist Philosophy educational experience with abandoned chidren from an institution named Foundação de Amparo ao Menor (FUNDANOR), fron the city of Palmeira dos Índios, in the state of Alagoas Brazil. We begin by critically investigating the fundamentals of the Program of the Philosophy for Children and Adolescents, which was created by the american philosopher and educator Matthew Lipman. Besides, we tried to bring together his proposal to Paulo Freire s Pedagogy. This is a historical-bibliographical research that was empirically developed with the assistence of a social in Popular Education. We also examinad to which extent methodology used in teaching of Pragmatist Philosophy accomplishs the plan of Alphabetization proposed by Paulo Freire s. Finally, we concluded that there is an aplication of Pragmatist Philososophy in Popular Education; so, it is an important tool in the process of developing a thoughtful set of questions concerning education. Besides, we realizad that it is a crucial point in the formation of philosophical, ethical and moral knowledges. Thus it is possible to bring together thet philosophy and Paulo Freire s Pedagogy.